The Impact of Information & Communication Technology on the Participation of Yemeni Women in Development in Light of the Sustainable Development Goals 2030 Indicators - Sabrin Saleh; Baseem Al-athwari; Abdu-alrazak Al-marani (International Journal of Computers and Informatics, 2024)
The study aimed to determine the impact of information and communications technology on the participation of Yemeni women in development in light of the indicators of the Sustainable Development Goals 2030. To achieve the objectives of the study, the study depends on the descriptive analytical approach, where a non-random, intentional sample is used that depends on the criterion of women’s participation in development and represents the institutions and governmental bodies in the governorates of Sana’a & Aden. A questionnaire was designed as a tool for collecting data and was distributed to the study sample, which numbered (230) individuals distributed among those entities participating in the study (215) valid questionnaires were retrieved that are capable of statistical analysis, Where the SPSS statistical program was used data analysis and hypothesis testing. The study reached to existence of a statistically significant effect of ICT in the participation of Yemeni women in development in the light of the indicators of SDGs of skills and costs dimensions and no impact of the infrastructure dimension. The results also showed significant impact on the impact of access to ICT on women's use of ICT regarding achieving SDGs. The study presented recommendations as enhancing the participation of Yemeni women in development by exploiting the opportunities provided by ICT in achieving SDGs by spreading awareness among Yemeni women of the importance of acquiring and developing their technological skills through various media to highlight the importance of technology in the economic, educational, cultural, health, community participation, decision support and other development fields.
Keywords: Information and Communications Technology; Participation; Sustainable Development